PROGRAM PERSIAPAN DAN PENGEMBANGAN BISNIS KULINER BAGI WIRAUSAHA MUDA DI KOTA BANDUNG - Maria Merry Marianti; Istiharini Istiharini; Deti Mulyo Harsono; Natalia Christi; Teresia Debby (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
The birth of young entrepreneurs in a region is considered very important because it can encourage local economic growth and create jobs. However, the current situation shows the tight business competition, especially in the culinary field in Bandung City. In an effort to help prospective entrepreneurs and young entrepreneurs compete in a competitive business environment, the Faculty of Economics, Parahyangan Catholic University, in collaboration with the First Baptist Church of Bandung held a business pre-incubation program for young entrepreneurs, which is expected to be a provision in developing innovative business ideas, building a business, and managing a business well. From the results of the pre-incubation program activities (training and mentoring) for young entrepreneurs in the culinary field in Bandung City, participants felt helped by the various materials presented in an easy-to-understand manner so that it is hoped that this program can help participants achieve business success in the future. “Keywords: Entrepreneur; Young Entrepreneur; Culinary Business”